Global value chain dependencies under the magnifying glass - Schwellnus, Cyrille (OECD Publishing, 2023)
Policy makers are increasingly grappling with the stability implications of global value chains (GVCs), as widespread supply shortages following the COVID-19 pandemic and the Russian Federation's large-scale aggression against Ukraine have disrupted the economic recovery and contributed to high inflation. This paper provides a tool to assess vulnerabilities in GVCs by drawing a detailed map of dependencies based on new indicators constructed from the OECD Inter-Country Input-Output tables. The key findings are as follows. First, GVC dependencies increase with both the size of foreign exposures and the length of foreign value chains. Second, in some industries, such as the automotive and ICT industries, vulnerabilities from high GVC dependence are amplified by high geographic concentration of suppliers or buyers. Third, the People's Republic of China is the most critical choke point in GVCs across a broad range of industries, both as a dominant supplier and as a dominant buyer
Keywords: Science and Technology; Economics; Trade; Industry and Services